(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
The earth is facing climate change because the temperature is getting higher and higher, and this is accelerated due to human activities, that is, we have driven humans and increased greenhouse gas emissions.Facing it requires a global commitment, in which all countries must reduce the emission of greenhouse gases into the atmosphere. For this, it is necessary to bet on renewable energy, public transport and cars that use clean energy, and pass laws that regulate emissions from the industry.